Key node decision algorithm based on local information and energy factor in wireless sensor network - Bin LIU; Ya-jing SUN; Hao-ran LIU; Rong-rong YIN (Tongxin xuebao)
In the existing key node decision methods for wireless sensor network,the judgment index was so single that the result judged was deficient.In order to solve this problem,a new key node decision algorithm(KNDA)based on local information and energy factor was proposed.Firstly,the local information model based on the degree and neighbor information of node was established.Secondly,according to the residual energy of node and the change of network energy consumption after the node failed,the models of energy factors were established.Finally,an aggregative key node decision model was formed.Extensive simulation experiments were carried out in the MATLAB simulation platform,by comparing with other algorithms,the results verify that the key nodes obtained by this algorithm are more sufficient.Meanwhile when the key nodes judged by KNDA are protected,the network can show strong invulnerability.